Cover Feature: An Improved Protocol for the Morita‐Baylis‐Hillman Reaction Allows Unprecedented Broad Synthetic Scope (Eur. J. Org. Chem. 9/2022). Issue 9 (21st February 2022) - Camilo, Nilton S.; Santos, Hugo; Zeoly, Lucas A.; Fernandes, Fábio S.; Rodrigues, Manoel T.; Silva, Thiago S.; Lima, Samia R.; Serafim, José Cláudio; de Oliveira, Aline S. B.; Carpanez, Arthur G.; Amarante, Giovanni W.; Coelho, Fernando
Abstract : The Cover Feature illustrates the effect of acetic acid on the rate of the Morita–Baylis–Hillman reaction. The use of acetic acid as a fuel (additive) increases the reaction rate in all tested cases, with special emphasis on electron‐rich electrophilic partners. We believe that a general acid catalysis mechanism is responsible for this increase in reaction rate. More information can be found in the Research Article by G. W. Amarante, F. Coelho et al .